Pendampingan Penerapan Hygiene dan Sanitasi pada Kantin Pertama Fakultas Kedokteran Universitas Mulawarman - Saroinsong, Yos Andreas; Utoro, Panggulu Ahmad Ramadhani (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M), Universitas Mulawarman, 2024)
Food safety is an effort to prevent the possibility of products being contaminated by biological, chemical, and physical contaminants. Food contamination is undesirable for both producers and consumers. This contamination occurs in micro small enterprises such as canteens. This activity focuses on Kantin Pertama at the Faculty of Medicine, Mulawarman University. This Community Service Program aims to provide education about hygiene and sanitation to the MSME (Micro, Small, and Medium Enterprises) at Kantin Pertama. This will ensure better quality and safety of the food and beverages produced in Kantin Pertama. The Community Service Program is carried out from December 19, 2023, to January 31, 2024, using three methods: first, socialization and discussion; second, observation and interviews; and third, problem-solving with assistance. Observation and interviews are conducted to identify issues occurring in the First Canteen. Then, problem-solving is carried out through assistance. The project was progressing smoothly. After completing the Class A1 food service questionnaire, we obtained a total score 62. However, after implementing the solution, the total score increased to 66, meeting the score range of 65-70.